The Influence of Brand Ambassador and Price Discount on Consumer Purchase Intention in E-Commerce Shopee (Case Study on Shopee Users in Bandung City) - Adam Faritzal; Widya Chandra Putri Aryani; Rizal Ramdan Padmakusumah; Santos Winarso Dwiyogo; Gina Apriyani Nurunnisha (Yayasan Ilomata, 2023)
This study aims to find out how the influence of Brand Ambassadors and price discounts on consumer purchase intentions in e-commerce Shopee (a case study of Shopee users in the city of Bandung). In this study, the independent variables were Brand Ambassador and price discount. While the dependent variable is purchase intention. The research method used in this research is descriptive and verification method. The population in this study are consumers who use e-commerce Shopee. The sampling technique used in this study was non-probability sampling using a purposive sampling technique with a total sample of 100 respondents. While the analytical method used in this study is the analysis of the Pearson product moment correlation coefficient and the coefficient of determination. The program used in analyzing the data uses the Statistical Package for Social Sciences (SPSS) Ver. 24.00. The results showed that the Brand Ambassador variable had an influence on purchase intention by 21.3% and the price discount variable had an influence on purchase intention by 29%. Furthermore, simultaneously the Brand Ambassador and price discount variables have an influence on purchase intention by as much as 34%.